Paningset, srah-srahan & midodareni / Suwarna Pringgawidagda ; penyunting, Hermawan Hastho Nuigroho. - SUWARNA PRINGGAWIDAGDA; Hermawan Hastho Nugroho (Adicita Karya Nusa, 2003)
x, 52 hlm. : ilus. ; 21 cm (3 eks.)